The effects of tetracaine on the membrane currents and contraction of frog atrial muscle. - Chapman, R A (1981)
1. The effects of tetracaine on the membrane currents and contraction of isolated frog atrial trabeculae under voltage clamp has been investigated. 2. Tetracaine inhibits the slow inward current in a competitive way with a Ki of 0.13 mM, and the phasic component of the contractile response in a non-competitive manner with a Ki of 0.25 mM. 3. The tonic phase of contraction is little affects by tetracaine while the outward current is reduced. 4. The effects of tetracaine on contraction closely resemble those obtained previously with K contractures and further emphasize that two processes, both of which depend on the membrane potential, are involved in the initiation of contraction in amphibian heart. 5. The effect of tetracaine on the phasic tension would seem to be due to an inhibition of both the slow inward current and the release of Ca2+ from the sarcoplasmic reticulum.